Electrical Signaling, Photosynthesis and Systemic Acquired Acclimation - Szechyńska-Hebda, Magdalena; Lewandowska, Maria; Karpiński, Stanisław (Frontiers in Physiology, 2017)
Electrical signalling in higher plants is required for the appropriate intracellular and intercellular communication, stress responses, growth and development. In this review, we have focus on recent findings regarding the electrical signalling, as a major regulator of the systemic acquired acclimation (SAA) and the systemic acquired resistance (SAR). The electric signalling on its own cannot confer the required specificity of information to trigger SAA and SAR, therefore, we have also discussed a number of other mechanisms and signalling systems that can operate in combination with electric signalling. We have emphasised the interrelation between ionic mechanism of electrical activity and regulation of photosynthesis, which is intrinsic to a proper induction of SAA and SAR. In a special way, we have summarised the role of non-photochemical quenching and its regulator PsbS. Further, redox status of the cell, calcium and hydraulic waves, hormonal circuits and stomatal aperture regulation have been considered as components of the signalling. Finally, a model of light-dependent mechanisms of electrical signalling propagation has been presented together with the systemic regulation of light-responsive genes encoding both, ion channels and proteins involved in regulation of their activity. Due to space limitations, we have not addressed many other important aspects of hormonal and ROS signalling, which were presented in a number of recent excellent reviews (e.g., Foyer and Noctor, 2013; Vaahtera et al., 2014; Dietz, 2015; Considine et al., 2015; Gilroy et al., 2016; Mignolet-Spruyt et al., 2016).